Students' Perceptions of the Physics-Mathematical E-Module on Partial Differential Material Based on Gender - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Wulandari, Mashelin (Jurnal Pendidikan dan Pengajaran, 2021)
Some obstacles in teaching and learning activities could be seen in the lack of teaching materials that students could easily understand. This is because the main books used are books in English as a whole. Therefore, the researcher developed an electronic book, namely the e-module of mathematical physics I on partial differential material created using 3D Page Flip Professional application. The type of research used is a comparative type of quantitative research. The population in this study were students of Physics education class 2019 with a sample of 80 regular classes A and B. The sampling technique used is simple random sampling. The data were analysed by descriptive and inferential statistics using IBM SPSS Statistic 25 application consisting of descriptive test, normality test, homogeneity test, and t-test. In the assumption test, the data is normally distributed and homogeneous so that a t-test can be performed. The t-test obtained a sig value of 0,043 for gender differences in class A and 0,010 for gender differences in class B. Therefore, it can be concluded that Ho is rejected and Ha is accepted, meaning that there are significant (significant) differences in perceptions based on gender in each class A and B. Meanwhile, the perception of female students is higher than the perception of male students, but overall students gave a good perception of the mathematics physics e-module on partial differential material.